THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN CYBERSECURITY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The rapid advancement of Artificial Intelligence (AI) has significantly impacted cybersecurity. This paper explores the use of AI technologies such as machine learning, deep learning, and natural language processing to address the growing complexity of cyber threats. These technologies improve the detection and prevention of cyberattacks, including malware analysis, phishing prevention, and intrusion detection. AI also automates the identification of anomalous behavior, enabling faster responses to emerging threats. However, integrating AI in cybersecurity introduces challenges such as adversarial attacks and data privacy concerns. The paper highlights the need for ethical considerations in applying AI to cybersecurity and stresses that AI’s risks and limitations must be carefully managed.